Assessment of Nutritional Status of Diabetic Patients in Ogun State, Nigeria - Adebisi, Tunrayo (American Journal of Human Ecology, 2013)
<!–[if gte mso 9]> <![endif]–> The study assessed the nutritional status of diabetic patients in Ogun State, Nigeria. Three research questions were used to guide the study. Two referral medical hospitals were used for the entire study. The out-patient departments of the Olabisi Onabanjo University Teaching Hospital, Sagamu (OOUTH) and the Federal Medical Centre, Idi-Aba, Abeokuta (FMCA) were used. The OOUTH covered the entire Ijebu division of Ogun State while FMCA covered the Egba division of Ogun State. A total of 90 respondents were recruited for the field survey and 37 (41.9%) of them were male while 53 (58.9%) were female. The female who were observed were 23 (43.4%) and the male were 5 (13.5%) showing a very great prevalence of obesity among the female. Lack of education was not the cause of diabetes mellitus. Based on the findings, it was revealed that only 5 (13.5%) male and 14 (26.4%) female had no formal education. Others had one level of education or the other. There is high prevalence of obesity among female respondents. Conclusion was drawn. Among the recommendations stated is that there should be urgent and serious enlightenment campaign by the ministry of health both at federal and state level so that people in the community will be more aware of the ailment. The campaign should also stretch to local government areas. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>